Improving the behavior of unsaturated polyester against wear by reinforcing it with thermoplastic polymers (Journal of the College of Basic Education, 2023)
This work includes preparation of composite materials and hybrids of unsaturated polyesters (UP) by reinforcing it with poly methyl metharcylate (PMMA) and high density polyethylene particles (HDPE) or (PE).These composites and hybrids were prepared by a hand-layup method with specific per cents.Wear test was carried on prepared polymeric composites and hybrids and their behaviour were studied.The study of wear was taken with respect to changing time with weight and its effect on density. The results show a remarkable behaviour in improving the behaviour of wear of unsaturated polyester after reinforcing by comparing this behaviour with plain unsaturated polyester sample.It was concluded that the wear of unsaturated polyester could be delay by reinforcing it with low cost materials like other polymers such as PMMA and HDPE